Correlation between the restoration method and the development of fractures in endodontically treated teeth - a study on panoramic radiographies - Anca-Elena But; Irina Maria Gheorghiu; Mihaela-Rodica Păuna (Amaltea Medical Publishing House, 2019)
The aim of this study is to identify the restoration methods used by dentists in Romania and to relate them to the development of coronal or mixed fractures. Materials and methods. 400 panoramic radiographies made between 2012 and 2017 were analyzed by an endodontics specialist. Teeth with endodontic treatment were identified and analyzed, their restoration method was noted and the fractures were detected. Results and discussions. The restoration methods preferred by the dentist in Romania are: dental bridges (35.72%), individual crowns (33.25%), fillings (28.64%) and a low percentage of onlays and other types of restorations. Fractures occur in less than 20% of the teeth, most of them from the lateral region. The main reasons for the appearance of fractures are: massive coronal direct restorations, bulky direct metallic posts that reduced the resistance of the roots, abutments and loosening of crowns. Conclusions. Endodontic treatments are more necessary in lateral teeth, direct fillings being the restoration method that led to the development of most of the fractures. Individual crowns have the lowest failure rates, while teeth without posts fractured twice as much as teeth that have them.